PENGARUH INTELLECTUAL CAPITAL DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN - Nenden Puspa Santiani (Jurusan Akuntansi Fakultas Ekonomi Universitas Siliwangi, 2018)
The aims of this research are to know: (1) The relationship between Intellectual Capital and Capital Structure, (2) The influence Intellectual Capital by partially to Firm Value, (3) The influence Capital Structure by partially to Fimr Value, (4) The Influence of Intellectual Capital and Capital Structure by simultaneously to Firm Value. This research object cover The Intellectual Capital, Capital Structure, and Firm Value on the financial statements of LQ45 Company listed in Indonesia Stock Exchange in 2016. Data anlysis in this survey are used path analysis. The results shows that: The relationship between Intellectual Capital and Capital Structure is not significant. Partially, Intellectual Capital have a positive and significant effect to Firm Value. Partially, Capital structure is not significant to Firm Value. In simultaneously, Intellectual Capital and Capital Structure have a influence significant to Firm Value.